Psychology and the School of Business Curriculum - Miner, John B. (Academy of Management Journal, 1963)
The article discusses the results of a survey on the types of services offered by psychologists in business schools and the advantages of having a knowledge of psychology in the business world. The author presents an overview of types of courses taught by psychologists, educational levels taught by psychologists, and theories they can introduce to the business school curriculum. A discussion is presented about the importance of a well-rounded curriculum and the management of a business school.